Identification of active sites and their redox strength to select products from photocatalysis in aqueous solutions - Van‐Can Nguyen; Chatiya Ardchon; Patthranit Wongpromrat; Yuh‐Lang Lee; Hsisheng Teng (Applied Catalysis B: Environmental, 2025)
Solar-driven photocatalytic H 2 evolution from aqueous solutions is promising for sustainable energy production, but it typically requires sacrificial electron donors to expedite the evolution. The fate and reaction pathways of these donors, especially their selective oxidation driven by active sites with distinct redox strengths, are rarely studied. The present study demonstrates that the reforming of sacrificial methanol in photocatalytic H 2 evolution can be directed toward selective production of value-added C 2 chemicals by tuning the redox properties of co-catalyst-derived active sites. Model catalysts, potassium poly(heptazine imide) (KPHI) decorated with Pt and CoP co-catalysts, i.e., Pt@KPHI and CoP@KPHI, are used to elucidate the reaction pathways, where acetate and ethylene glycol are the predominant liquid-phase products, respectively, alongside the gaseous H 2 evolution. In the Pt@KPHI system, Pt serves as a strong electron trap to effectively reduce water into H 2 and methanol into • CH 3 and induces hole-driven deep oxidation of methanol into • CO 2 ⁻ on KPHI. The C−C coupling of • CH 3 and • CO 2 ⁻ radicals selectively forms acetate. In the CoP@KPHI system, CoP served as a mild hole trap to proceed with methanol dehydrogenation into • CH 2 OH radicals and then ethylene glycol, while mild reduction takes place over KPHI to produce H 2 , presenting parallel redox reactions without any interaction. Our work illustrates how co-catalyst-induced active sites govern charge transfer and interaction between the redox reactions, thus selectively producing valuable chemicals from H 2 -evolution photocatalysis. • Co-catalysts dictate value-added C 2 selectivity in photocatalytic methanol reforming. • Active sites with tuned redox strengths control radical pathways. • Pt@KPHI with strong e - -trap Pt drives • CH 3 and • CO 2 ⁻ radicals to form acetate. • CoP@KPHI with mild h + -trap CoP directs • CH 2 OH pathways to ethylene glycol. • Co-catalyst design enables tunable solar H 2 and C 2 chemical production.
Keywords: Advanced Photocatalysis Techniques; TiO2 Photocatalysis and Solar Cells; Electrochemical Analysis and Applications